Empowering Coastal Voices: AI-Powered Podcasting for Inclusive Communication in Kepulauan Seribu - Wiratri Anindhita; Salsabila Haura Zhafirah (Journal of Communication and Public Relations, 2026)
This study aims to explore artificial intelligence (AI)-based communication in supporting inclusive communication through podcast media in the coastal areas of the Thousand Islands (Kepulauan Seribu). As an archipelagic region administratively part of the Jakarta Special Capital Region (DKI Jakarta) and consisting of small islands scattered across the northern waters of Jakarta, the Thousand Islands face significant geographical challenges, including limited access to information, inadequate technological infrastructure, and low community engagement in national digital communication flows. In this context, podcasts emerge as an alternative communication medium that is cost-effective and easily accessible, enabling coastal communities to directly convey their voices, experiences, and local issues. One local media outlet that plays a key role in this process is Radio Kepulauan Seribu (RKS), a community radio station that has long served as the primary link between island residents and local information sources. However, RKS faces substantial challenges related to limited human resources, both in terms of staff numbers and technical skills required for sustainable digital content production. In response to these constraints, the adoption of AI technology becomes highly relevant in supporting the continued production of podcast content. Technologies such as text-to-speech and speech-to-text assist in converting text into audio and vice versa, allowing community members to produce podcast content even without formal broadcasting skills. In addition, Natural Language Processing (NLP) is utilized to support script drafting, translate local languages into Indonesian, and identify key terms relevant to community needs. This study employs a qualitative descriptive approach and was conducted in several coastal communities connected to RKS and local educational institutions. Informants include community radio broadcasters, educators, and community members actively involved in the production or consumption of digital audio content. The findings indicate that the application of AI in podcasting not only facilitates technical aspects of content production but also expands broadcast reach across digital platforms such as Spotify, YouTube, Instagram, and WhatsApp. AI-supported podcasting enables faster production processes, more diverse content, and more engaging delivery of local messages, even when managed by a small team. Thus, this communication model represents a contextual and adaptive strategy in response to digital technological developments while empowering coastal communities to become active actors in independently voicing their local interests and identities.